Enhancing Educational Courses through A Collaborative Learning Management System: A Study on Effectiveness - Tukiyo Tukiyo (STAI Hubbulwathan Duri, 2024)
This study evaluates the effectiveness of a collaborative learning model integrated with a learning management system in diverse educational contexts. The issue of suboptimal student learning outcomes is often attributed to deficiencies in the development of instructional models and media. The critical role of instructional media in achieving successful learning outcomes necessitates research to bridge the gaps between actual knowledge, theoretical expectations, and practical applications. This study aims to enhance educational models and materials by employing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework for Research and Development. It involved 35 education students and adopted methods such as expert validation, lecturer feedback, and pre-and post-test evaluations for data collection. The analysis covered design, development, testing, and evaluation stages, confirming the developed model's efficacy and functionality. Evaluations by experts in technology and learning models, alongside peer assessments, supported the model's high effectiveness. Preliminary experiments achieved an average score of 88.